Formononetin alleviates acute pancreatitis by reducing oxidative stress and modulating intestinal barrier - Jun Yang; Xiaowei Sha; Di Wu; Bo Wu; Xiaohua Pan; Li-Long Pan; Yuanlong Gu; Xiaoliang Dong (BMC, 2023)
Abstract Background Acute pancreatitis (AP) is a recurrent inflammatory disease. Studies have shown that intestinal homeostasis is essential for the treatment of AP. Formononetin is a plant-derived isoflavone with antioxidant properties that can effectively treat a variety of inflammatory diseases. This study aims to investigate the role of formononetin in protecting against AP and underlying mechanism. Methods Caerulein was used to induce AP. The inflammatory cytokines were detected using Quantitative real-time PCR and commercial kits. Histological examination was applied with hematoxylin and eosin staining. Western blot was conducted to detect expression of intestinal barrier protein and signaling molecular. Molecular docking was performed to assess protein-ligand interaction. Results In this study, we found formononetin administration significantly reduced pancreatic edema, the activities of serum amylase, lipase, myeloperoxidase, and serum endotoxin. The mRNA levels of inflammatory cytokines such as tumor necrosis factor α, monocyte chemoattractant protein-1, interleukin-6, and interleukin-1 beta (IL-1β) in pancreas were also significantly decreased by formononetin. The following data showed formononetin pretreatment up-regulated the expressions of tight junction proteins in the colon, and decreased Escherichia coli translocation in the pancreas. In addition, formononetin inhibited the activation of nucleotide-binding oligomerization domain leucine-rich repeat and pyrin domain-containing 3 in pancreatic and colonic tissues of AP mice. Moreover, formononetin activated Kelch Like ECH Associated Protein 1 (Keap1) / Nuclear factor erythroid2-related factor 2 (Nrf2) signaling pathway to reduce reactive oxygen species (ROS) levels. Docking results showed that formononetin interact with Keap1 through hydrogen bond. Conclusions These findings demonstrate that formononetin administration significantly mitigate AP through reducing oxidative stress and restoring intestinal homeostasis, and provide insights into the new treatment for AP.